Prevention and Mitigation of Medical Error by Nursing Staff at Zliten Medical Center - Mihat, Mabroka Mohammed; Algedar, ِِAhmed A.; Mihat, Marwa Abd Al-Salam; Jaber, Nora Ahmed; Algwel, Donia Salim (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study main objective is to ensure patient safety. Medical mistake has a negative impact on patient safety and is a significant health concern in healthcare systems. As essential members of the healthcare team, nurses are crucial in minimizing these mistakes and limiting other types of errors, such as making the correct responsible decisions. The study's objectives were to guarantee patient safety and raise the standard of healthcare, prevent and mitigate of the medical error. The response was 60 nursing staff from Al-Hayat Medical Hospital and Zliten Medical Center had their information gathered. The findings demonstrated that the department's lack of nursing staff contributed to patient neglect, with a high relative weight of response. Additionally, the nurse's work was neglected due to complex administrative procedures. The study concluded that Increasing the number of nurses on staff at the hospital while accounting for nursing enhance to ensure the work to the high level of quality. Increasing the sufficient number of nursing staff in the hospital. Facilitates complex administrative procedures while taking into account nursing scheduling so that work hours are appropriate to their ability.
Keywords: Nursing mistakes; Mitigate; Patient; Prevention; Hospital